Lightpath reconfiguration with traffic priority consideration. (29th June 2009) - Sumathi, M.; Vanathi, P.T.
Optical fibre supports large bandwidth applications such as grid computing and e-science that require reliable optical paths. The network carries data belonging to these high priority applications as well as that of applications such as e-mail and file transfer protocol, which are of lower priority. The optical network is reconfigured in order to optimise the network performance, and lightpaths are setup and torn down based on the traffic flow. The lightpaths of high priority applications must not be disrupted during reconfiguration. Therefore, an algorithm is proposed for reconfiguration of an optical network, in which lightpaths are setup between node pairs carrying traffic belonging to high priority applications, on a priority basis and are not disrupted during the entire session. Simulation results show that using the proposed algorithm, the value of average weighted hop count (AWHC) is maintained at approximately one for high priority applications.